2010
DOI: 10.1111/j.1600-0722.2009.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element and Weibull analyses to estimate failure risks in the ceramic endocrown and classical crown for endodontically treated maxillary premolar

Abstract: The present study evaluated the failure risks of an endodontically treated premolar with severely damaged coronal hard tissue and restored with either a computer-aided design/computer-aided manufacturing (CAD/CAM) ceramic endocrown or a classical crown configuration. Two, three-dimensional finite element maxillary premolar models were designed with endodontic treatment and restored with either a chairside economic reconstruction of esthetic ceramic (CEREC) ceramic endocrown or a classical crown. The Weibull fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 25 publications
4
82
0
8
Order By: Relevance
“…In previous studies, there has been considerable disagreement about the endocrown as an available method for premolars. Some studies found that endocrowns for endodontically treated maxillary premolars had higher fracture resistance than the conventional restorations,1617 while others reported that endocrowns appeared inadequate for premolars compared with conventional crowns 2021. Moreover, there has not been any recommendation about the validity of the endocrown for endodontically treated mandibular premolars, which have quite different anatomic forms from maxillary premolars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, there has been considerable disagreement about the endocrown as an available method for premolars. Some studies found that endocrowns for endodontically treated maxillary premolars had higher fracture resistance than the conventional restorations,1617 while others reported that endocrowns appeared inadequate for premolars compared with conventional crowns 2021. Moreover, there has not been any recommendation about the validity of the endocrown for endodontically treated mandibular premolars, which have quite different anatomic forms from maxillary premolars.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have reported that molars and maxillary premolars with ceramic endocrowns showed better fracture resistance than those with conventional postcore supported ceramic crowns 151617. However, there were few studies about the fracture strength of endocrowns of the mandibular premolars, whose coronal and radicular geometries are quite different from their maxillary counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has shown promising results and comparable short-term survival when compared to post, core, and crown systems. [18][19][20][21][22] A wide collection of ceramic materials has been available for CAD/CAM technology, ranging from relatively weak feldspathic ceramic and leucite glass ceramic to high-strength lithium disilicate glass ceramic and zirconium oxide. 23 Most recently, a resin nanoceramic has been introduced for permanent CAD/CAM fabricated restorations.…”
Section: Introductionmentioning
confidence: 99%
“…This result was in agreement with other studies which observed higher fracture loads for endocrowns compared to fiber post and core supported crowns. (13,19,22) The root resistance to fracture is directly related to the volume of remaining dentin. (23) Study was reported that thicker root dentin walls significantly increase the fracture resistance of endodontically treated teeth.…”
Section: Discussionmentioning
confidence: 99%
“…(12) The surfaces available within the pulp chamber obtain stability and retention of the restoration through adhesive bonding. (13) This type of restoration can be fabricated through computeraided design/computer aided manufacturing (CAD/ CAM) technology, providing the possibility for chair-side design and fabrication. (14) The advantages of endocrowns over foundation restorations can be summarized as follows: they reduce the interfaces of the restorative systems, they have ability of restoring teeth with insufficient vertical dimension, they can restore badly broken down teeth while preserving the maximum tooth structure rendering more efficient and aesthetic results and they also reduce the need for macroretentive geometry.…”
Section: Introductionmentioning
confidence: 99%